Identifying patterns of kinesiophobia trajectories among COPD patients: A longitudinal study - Facun Liang; Mengru Liu; Hui Han; Yunxin Ru; Yanru Yin; Chen Cheng; Meng Xue; Lifang Gu (Nursing Open, 2023)
Abstract Aim To determine differences in kinesiophobia levels among COPD patients at different time points 6 months after discharge；To identify potential subgroups of COPD patients who perceived different levels of kinesiophobia over time；and to evaluate differences in identified subgroups based on demographic and disease‐related characteristics Design An observational longitudinal study. Methods OPD patients hospitalized in respiratory department of a grade A hospital in Huzhou city from October 2021 to May 2022 were selected as the research objects. TSK scale was used to evaluate the level of kinesiophobia at discharge (T1), 1 month after discharge (T2), 4 months after discharge (T3) and 6 months after discharge (T4). The kinesiophobia level scores at different time points were compared using latent class growth modelling. ANOVA and Fisher's exact tests were used to test differences in demographic characteristics，and univariate analysis and multinomial logistic regression analysis were used to explore the influencing factors. Results During the first 6 months after discharge, kinesiophobia levels decreased significantly in the entire sample of COPD patients. The best‐fitting group‐based trajectory model described three distinctive trajectories: Low kinesiophobia group (31.4% of sample); Medium kinesiophobia group (43.4% of sample)；and High kinesiophobia group (25.2% of sample). Logistic regression results showed that sex, age, course of disease, pulmonary function, education level, BMI, the level of pain, MCFS and mMRC were influencing factors of kinesiophobia trajectory in COPD patients (p < 0.05).